Department Chairs: More Than Floating Heads with Absent Hearts - Summer Juliet Cowley (Canadian Society for Studies in Education, 2018)
There is a tendency in discussions of higher education to treat the human administrators who run universities as solely rational subjects, separated from their idiosyncrasies, preferences, and emotions (Mumby & Putnam, 1992; Luthar & Šadl, 2008). In this paper, I argue that department chairs, as people managers, should be conceptualized as playing significant emotional role, rather than as solely serving instrumental functions as "bean counter[s]" (Chu, 2011, p. 52). In this paper, I argue that: 1) the role of chair is important and emotional; 2) leadership theories lack agreement on best ways to lead; and 3) department chairs are emotion workers. I close this paper by stating that department chairs need to be considered as performing work that demands ongoing emotional self-management and that research on chairs should have a dual focus of task-oriented and emotion work-oriented inquiry.